2002
DOI: 10.1023/a:1014737831371
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Biological properties of titanium implant depend on its surface oxide film. In the present study, the surface oxide films on titanium were characterized and the relationship between the characterization and bioactivity of titanium was studied. The surface oxide films on titanium were obtained by heat-treatment in different oxidation atmospheres, such as air, oxygen and water vapor. The bioactivity of heat-treated titanium plates was investigated by immersion test in a supersaturated calcium phosphate solution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
55
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(70 citation statements)
references
References 14 publications
6
55
0
Order By: Relevance
“…However, titanium is a bioinert material that neither chemically connects to bone nor actively induces bone growth. Therefore, various surface modifications of titanium implants have been carried out to improve its bioactivity [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…However, titanium is a bioinert material that neither chemically connects to bone nor actively induces bone growth. Therefore, various surface modifications of titanium implants have been carried out to improve its bioactivity [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The revealed peaks at 529 or 530 eV can be attributed to oxygen of the surface oxide layer of TiO 2 (Ti-O) [32,33]. Surface acidic and basic hydroxyl groups (531 and 532 eV) are bound to two surface titanium atoms, whereas the basic OH (532 or 534 eV) is bound to one surface titanium atom [34][35][36]. In all high resolution scans, the major contribution to the O1s peak resulted from the formation of Ti-O.…”
Section: Surface Chemical Analysesmentioning
confidence: 99%
“…It is reported that bacterial cells have the highest affinity for rutile. The reasons speculated include the reported [42] increase in the bioactivity of the rutile surface due to heat treatment. Feng et al report that rutile TiO 2 forms at higher temperatures and that during heat treatment, oxygen and water react with the titanium surface, increasing the amount of hydroxyl groups on the surface and also thickening of the oxide film.…”
Section: Evaluation Of Anti-biofilm Propertymentioning
confidence: 99%